Study Chinese Teenagers' Character Education from Six Dimensions: Analysis of Survey Data - Zhang, Lingmin (MASI Mandiri Edukasi, 2024)
Because the formation and development of human character are influenced by family, school, society, network, and peers, this paper studies the influence of these dimensions on youth character education to understand the current situation of youth character education and grasp the dimensions that youth character education should focus on. This paper examines the influence of the six dimensions of family, school, society, network, peer, and self on adolescent character education and the relationship between these six dimensions. This paper's quantitative research method finding: most respondents believed that family education significantly impacted teenagers' personalities, that teenagers attach the most importance to their personality, even more than schools and families, but the Internet attaches little importance to personality education and is most supportive of character education at school and home. This study will expand the dimension of youth quality education and has practical value for strengthening the joint education system.